Retooling and reskilling for school libraries in the 4th industrial revolution era: implications for school library media specialists. (2020)
The world has witnessed three different revolutions in the past and currently witnessing the 4th revolution. Revolution simply means drastic changes in the way things are done. The 4th Industrial Revolution (4thIR) is known as knowledge society which built upon the digital revolution. It is a combination of technologies that cover the lines between the physical, digital, and biological domains. It has brought a wave to human endeavours, the changes brought are enormous in the way people communicate, interact and behave which is referred to as the ‘new normal’. As a result, all human systems have adjusted and adapted to the new normal, in particular, the educational system has been highly transformed and it has affected libraries, the heartbeat of any educational institution. Thus, school libraries collections, environments, and services have been transformed and it calls for reskilling of School Library Media Specialists (SLMSs) who are the managers of school libraries. On this note, this paper discusses the emerging technologies for school libraries in the 4th Industrial revolution, new roles of SLMSs and the skills required of the School Library Media Specialists to function in the 4th IR era. Recommendations are proffered based on the reality of the new normal